Implementasi Program Life Skill Memasak Sebagai Upaya Menumbuhkan Kewirausahaan Berbasis Food And Beverage Peserta Didik Paket C Di PKBM Budi Utama Surabaya - Ramadhan, Nova (Universitas Negeri Surabaya, 2024)
This research aims to describe efforts to implement cooking life skills at PKBM Budi Utama Surabaya and the efforts made by PKBM to foster food and beverage-based entrepreneurship among students. This type of research is descriptive research with a qualitative approach. The subjects of this research were the Head of PKBM, Tutors and Package C Learning Residents. The data collection techniques used were in-depth interviews, observation and documentation studies. The data analysis used uses the Miles and Huberman theory, namely data condensation, data display and drawing conclusions. The validity of the data is carried out by testing credibility, dependability, confirmability and transferability. The research results show that PKBM's efforts to foster food and beverage-based entrepreneurship are successful. PKBM provides full facilities during program implementation. Many learning residents are motivated to establish entrepreneurship and develop entrepreneurship after gaining knowledge from PKBM. Keywords: Program implementation, Life skills, Entrepreneurship